Factors Of Development Of Logical And Critical Thinking Of Adolescents - Ummatkulova, Nigora Umarkulovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes the theoretical and practical aspects of the development of logical and critical thinking in adolescence. The important factors in the intellectual development of adolescents, in particular, the role of the educational environment, pedagogical approaches, family influence and modern technologies, are highlighted. Effective methods for developing independent thinking skills in adolescents are also considered.